Tomato Divinyl Ether-Biosynthesis Pathway Is Implicated in Modulating of Root-Knot Nematode Meloidogyne javanica's Parasitic Ability - Sanadhya, Payal; Kumar, Anil; Bucki, Patricia; Fitoussi, Nathalia; Carmeli-Weissberg, Mira; Borenstein, Menachem; Brown-Miyara, Sigal (Frontiers in Plant Science, 2021)
The role of the 9-lipoxygenase-derived oxylipins in plant defense is mainly known in solanaceous plants. In this work, we identify the functional role of the tomato divinyl ether synthase (LeDES) branch, which exclusively converts 9-hydroperoxides to the 9-divinyl ethers (DVEs) colneleic acid (CA) and colnelenic acid (CnA), during infection by the root-knot nematode Meloidogyne javanica. Analysis of LeDES expression in roots indicated a concurrent response to nematode infection, demonstrating a sharp increase in expression during the molting of third/fourth-stage juveniles, 15 days after inoculation. Spatiotemporal expression analysis using an LeDES promoter:GUS tomato line showed high GUS activity associated with the developing gall; however the GUS signal became more constricted as infection progressed to the mature nematode feeding sites, and eventually disappeared. Wounding did not activate the LeDES promoter, but auxins and methyl salicylate triggered LeDES expression, indicating a hormone-mediated function of DVEs. Heterologous expression of LeDES in Arabidopsis thaliana rendered the plants more resistant to nematode infection and resulted in a significant reduction in third/fourth-stage juveniles and adult females as compared to a vector control and the wild type. To further evaluate the nematotoxic activity of the DVEs CA and CnA, recombinant yeast that catalyzes the formation of CA and CnA from 9-hydroperoxides was generated. Transgenic yeast accumulating CnA was tested for its impact on M. javanica juveniles, indicating a decrease in second-stage juvenile motility. Taken together, our results suggest an important role for LeDES as a determinant in the defense response during M. javanica parasitism, and indicate two functional modes: directly via DVE motility inhibitioneffect and through signal molecule-mediated defense reactions to nematodes that depend on methyl salicylate.